The Implementation of Project Based Learning to Improve Students’ Mathematical Understanding and Learning Interest on Junior High School - Hazim, Muhamad; Yuliani, Anik; Setiawan, Wahyu ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
Mathematics is a lesson regarded regularly, logically, tiered from the easiest to the most complicated. Mastery and students’ understanding of a material can be seen from student mathematical abilities. Analyze the student’s error in completing the problem can know the students master a matter or not. The purpose of this research is 1) to describe students’ understanding of transformation material after following the Project Based Learning model, 2) to find out whether there is an increase in understanding of transformation after implementing the Project Based Learning process, 3) to find out how effective the approach method (Project Based Learning) is about the learning process on transformation material, 4) find out how to increase students’ understanding skills after implementing a project-based learning model. This research method uses classroom action research. Students can participate in learning activities using the PJBL approach very well, so that teaching and learning activities are conducive when implemented and the results from cycles 1 and 2 increase.